Functional dependence and the mental dimension of quality of life in Hemodialysis patients: the PROHEMO study - Gabriel Brayan Gutiérrez-Peredo (Health and Quality of Life Outcomes, 2020)
Abstract Background Functional dependence is highly prevalent in maintenance hemodialysis (MHD) settings. Also, poor health-related quality of life (HRQoL) and high levels of depressive symptoms have been reported by MHD patients. We investigated associations between functional status and mental aspects of quality of life in Brazilian MHD patients. Methods Cross sectional study of 235 patients enrolled in two of the four participating MHD clinics of the Prospective Study of the Prognosis of Chronic Hemodialysis Patients (PROHEMO) in Salvador, BA, Brazil. Data were collected from September 2016 to August 2017. The Katz’s questionnaire was used for basic activities of daily living (ADL) and the Lawton-Brody’s questionnaire for instrumental activities of daily living (IADL). ADL and IADL scores were combined to create 3 functional status groups: highly dependent (n = 47), moderately dependent (n = 109) and independent (n = 82). The validated Brazilian version of the Kidney Disease Quality of Life Short Form (KDQOL-SF) was used for scores of two distinct HRQoL measures, i.e., the mental component summary (MCS) and the 5-item mental health inventory (MHI-5). We used linear regression to estimate differences in scores with adjustment for possible confounders: months of dialysis, age, gender, other sociodemographic variables, body mass index, type of vascular access, dialysis dose by Kt/V, laboratory variables (albumin, blood hemoglobin, calcium, phosphorus, urea, creatinine and parathyroid hormone) and nine comorbid conditions. Results Mean age was 51.2 ± 12.4 yr (median age = 51.0 yr), 59.1% were male, 93.2% were non-White. The prevalence of self-reported functional status differed by age: 54.4% for age < 45 yr, 67.8% for age 45–60 yr and 73.9% for age ≥ 60 yr. Using functionally independent as reference, lower scores were observed for highly dependent patients in MCS (difference: -4.69, 95% CI: -8.09, -0.29) and MHI-5 (difference: -5.97, 95% CI: -8.09, -1.29) patients. These differences changed slightly with extensive adjustments for covariates. Conclusions Our results call attention to a high prevalence of functional dependence in younger and older MHD patients. The results suggest that the lower self-reported mental quality of life in functionally dependent MHD patients cannot be explained by differences in age and comorbidities.